Impact of Fertility and Mowing on Crabgrass Quantity and Quality for Hay Production in Southeast Kansas - B. C. Pedreira; D. Helwig; M. Haywood; J. K. Farney; G. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2022)
A crabgrass variety trial comparing Quick-N-Big and Mojo crabgrasses was conducted in 2021 at the K-State Experiment Station outside of Columbus, KS. The trial evaluated forage quantity and quality under different fertilization and harvest management practices.
Keywords: fertilizer; nitrogen; annual grass; crude protein